Answer:
Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}2y=-x+9\\3x-6=-15&\text{add 6 to both sides}\end{array}\right\\\left\{\begin{array}{ccc}2y=-x+9\\3x=-9&\text{divide both sides by 3}\end{array}\right\\\left\{\begin{array}{ccc}2y=-x+9\\x=-3\end{array}\right\qquad\text{put the value of x to the first equation}\\\left\{\begin{array}{ccc}2y=-(-3)+9\\x=-3\end{array}\right\\\left\{\begin{array}{ccc}2y=3+9\\x=-3\end{array}\right\\\left\{\begin{array}{ccc}2y=12&\text{divide both sides by 2}\\x=-3\end{array}\right\\\left\{\begin{array}{ccc}y=6\\x=-3\end{array}\right[/tex]